PENGUJIAN PERUBAHAN GAMBARAN EKG DAN TEKANAN DARAH SEBELUM DAN SESUDAH PEMBERIAN OMEGA 3 DAN BEBAN LATIHAN PADA MAHASISWA PEROKOK - Sari Luthfiyah; Dwi Herry Andayani; Liliek Sutjiatie (JURNAL PENELITIAN KESEHATAN, 2016)
Demographic Institute University of Indonesia said, the number of deaths arising from a disease that was caused by cigarette in 2004, as many as 427,948 people, it means that as many as 1,172 people per day (22.5 per cent) of the total amount death occurred in Indonesia (Bustan Festival, 2007).  One of the danger of the result smoking can cause a tendency blood clotting, so it can increase the risk peripheral arterial disease, the occurrence of coronary artery, and stroke. According to Fadilah Supari, cardiologist at Harapan Kita Hospital Jakarta, that those who consume, these platelets omega3 blood () not to break easily or bank. This research done in order to know test result changes the picture ecg and blood pressure before and after the omega3 heart muscles exercise and the burden on students smokers. This Research using experimental method with pure form design " Pretest-Postest Control Group Design".  Results of the study showed that in table trial normality with One-Samples Kolmogorov- Smirnov Test can be seen that the two groups depth distributed normal, while Independent result table Sample Test, shows that the two groups data have variance a Heterogeneous because the Gis in the fields Levene's Test for Equality Variances because 0.05 . In the attached table frequency found that most of the students groups treatment or groups control have Sistole 120 and diastole 80, which is shown with median. The mode that showing the number 1 means most among treated group there are ST elevation in ecg before consumption Omega3 and before heart muscles are given a training center. While a student group controls, entirely, elevation ecg before heart muscles are given a training center. A comparison Sistole and Diastole in the current treatment after Omega3 group and control, with the difference of the score Post and Pre heart muscles burden exercise in the attached table, comparative Independent test would t-test the Gis (2-tailed) each showing the number 0,843 and 0,512 . A comparison between groups result recording ecg treatment after giving Omega3 with the group control after heart muscles are given a training center in the attached table, Crosstabulation, found the Fisher's Exact of 1,000 . this means that it can be concluded that there is no difference of difference Sistole and Diastole as well as the EKG between treatment and groups control, because the Gis (2-tailed) 0,050 . Key words : Testing ecg and blood pressure, smoker student